The feasibility of using mutation detection in ctDNA to assess tumor dynamics - Yi, Xin; Ma, Jianhui; Guan, Yanfang; Chen, Rongrong; Yang, Ling; Xia, Xuefeng (International journal of cancer, 2017)
For many decades it has been known that tumor DNA is shed into the blood. As a consequence of technological limitations, researchers were unable to comprehensively characterize circulating DNA. The advent of ultrasensitive and highly specific molecular assays has provided a comprehensive profile of the molecular characteristics and dynamics of circulating DNA in healthy subjects and cancer patients. With these new tools in hand, significant interest has been provoked for an innovative type of tumor biopsy termed a “liquid biopsy”. Liquid biopsies are obtained by minimal invasive blood draws from cancer patients. Circulating cancer cells, exosomes and a variety of molecules contained within the liquid biopsy including cell‐free circulating tumor DNA (ctDNA) can serve as promising tools to track cancer evolution. Attractive features of ctDNA are that ctDNA isolation is straightforward, ctDNA levels increase or decrease in response to the degree of tumor burden and ctDNA contains DNA mutations found in both primary and metastatic lesions. Consequently, the analysis of circulating DNA for cancer‐specific mutations might prove to be a valuable tool for cancer detection. Moreover, the capacity to screen for ctDNA in serial liquid biopsies offers the possibility to monitor tumor progression and responses to therapy and to influence treatment decisions that ultimately may improve patient survival. Here we focus on mutation detection in ctDNA and provide an overview of the characteristics of ctDNA, detection methods for ctDNA and the feasibility of ctDNA to monitor tumor dynamics. Current challenges associate with ctDNA will also be discussed.